Pengaruh Efektivitas Kerja, Efisiensi Kerja Terhadap Kinerja Pegawai Dengan Work Life Balance Sebagai Variabel Intervening Padasekretariat Daerah Kabupaten Pasaman - Rahmalia Farah Diza; Hilda Mary; Nia Nadilla (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of work effectiveness and work efficiency on employee performance with work life balance as an intervening variable at the Regional Secretariat of Pasaman Regency. The research applies a quantitative approach using a survey method through questionnaires distributed to 105 respondents. Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with SmartPLS software. The results indicate that work effectiveness has a positive and significant effect on work life balance and employee performance. Work efficiency has a negative and insignificant effect on work life balance and employee performance. Work life balance has a positive and significant effect on employee performance. Indirectly, work effectiveness significantly influences employee performance through work life balance, while work efficiency does not show a significant indirect effect. The contribution value of work effectiveness and work efficiency to work life balance is 86.4%, and to employee performance is 63.9%. These findings emphasize that improving work effectiveness and maintaining work life balance are key factors in enhancing employee performance in government institutions.